1999
DOI: 10.1021/jp9906177
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of NO with CH4 Effected by Copper Oxide Clusters in the Channels of ZSM-5

Abstract: Fine structures of the copper oxide clusters involved in catalytic reduction of NO were studied by X-ray absorption spectroscopy. The Extended X-ray absorption fine structural (EXAFS) spectra indicate that about 2.89 nearest oxygen atoms bond to the Cu central atoms with a Cu-O bond distance of 1.96 Å for the oxidized Cu-ZSM-5 catalyst. Reduction of the catalyst in hydrogen at 573 K led to the formation of mainly Cu-Cu (2.54 Å) species with the coordination number (CN) of 2.91. The Cu 4 O 2 clusters in the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…X‐ray absorption near edge structure spectroscopy can also provide information of oxidation states of an excited atom, the coordination geometry, and the bonding of its local environment in environmental solids. By in situ EXAFS, we found that Cu oxides (in ZSM‐5 or ZSM‐48) were involved in the catalytic decomposition of NO (Huang and Wang, 1999; Huang et al, 2003) and oxidation of chlorophenols in supercritical water (Lin and Wang, 1999, 2000). Speciation of CuO during mineralization of CCl 4 was also studied by in situ EXAFS spectroscopy (Chien et al, 2001).…”
mentioning
confidence: 99%
“…X‐ray absorption near edge structure spectroscopy can also provide information of oxidation states of an excited atom, the coordination geometry, and the bonding of its local environment in environmental solids. By in situ EXAFS, we found that Cu oxides (in ZSM‐5 or ZSM‐48) were involved in the catalytic decomposition of NO (Huang and Wang, 1999; Huang et al, 2003) and oxidation of chlorophenols in supercritical water (Lin and Wang, 1999, 2000). Speciation of CuO during mineralization of CCl 4 was also studied by in situ EXAFS spectroscopy (Chien et al, 2001).…”
mentioning
confidence: 99%
“…A bump in the pre-edge region and an obvious shoulder in the edge jump were observed in XANES spectra of tetrahedral complex. The preedge XANES spectra of the Cu-contaminated soil exhibited a very weak absorbance band for the 1s to 3d transition (8975-8980 eV) which is forbidden by the selection rule in the case of perfect octahedral symmetry (Denise et al, 1989;Lin & Wang, 1999;Huang & Wang, 1999;Lin & Wang, 2000). A shoulder at 8984-8988 eV and an intense feature at about 8995-9002 eV were attributed to the 1s to 4p transition that indicated the existence of Cu(II) species.…”
Section: Resultsmentioning
confidence: 99%
“…EXAFS can provide structural information including the coordination number, bond distance, and oxidation state (Yu et al, 1990;Oday et al, 1994;Mosselmans et al, 1995;Foster et al, 1998). By EXAFS, we found that copper oxides involved in the catalytic decomposition of NO (Huang and Wang, 1999) and oxidation of chlorophenols in supercritical water (Lin and Wang, 1999). These molecular scale data were very useful in revealing the structure of catalysts in the catalysis process.…”
Section: Introductionmentioning
confidence: 83%